Dietary heavy metal exposure of Finnish children of 3 to 6 years. Issue 7 (3rd July 2018) - Suomi, Johanna; Tuominen, Pirkko; Niinistö, Sari; Virtanen, Suvi M.; Savela, Kirsti
ABSTRACT: The dietary exposure of Finnish 3-year-old and 6-year-old children to cadmium, lead, arsenic and mercury was determined using concentration data from Finland and individual food consumption data as well as individual weights of the children. Using middle bound estimates, 88% of the 3-year-olds and 64% of the 6-year-olds exceeded the tolerable weekly intake of cadmium. The benchmark dose for neurological damage caused by lead was exceeded by 14% and 1%, while the lowest benchmark dose of inorganic arsenic was exceeded by 43% and 29% for the 3-year-olds and 6-year-olds, respectively. The exposure of both age groups was below the tolerable weekly intake for inorganic mercury and methyl mercury. Although high, the exposures calculated with predominantly national concentration data were lower than previously estimated by EFSA, due to, for example, lower average concentrations in some much-consumed foods. The heavy metal exposure levels of the girls and the boys were also compared. Exposure to cadmium and lead was significantly higher for the boys than for the girls in both age groups, and exposure to inorganic arsenic was significantly higher for the 6-year-old boys than the girls of same age. Graphical Abstract: